Plastic but not progressive changes in cognitive function and hippocampal volume in an adolescent with bipolar disorder: a case report - Bo Liu; Bo Liu; Hui Sun; Hui Sun; Hui Sun; Qiannan Zhao; Qiannan Zhao; Qiannan Zhao; Li Li; Rong Tian; Su Lui; Su Lui; et al. (Frontiers in Psychiatry)
Bipolar disorder (BD) is a prevalent mood disorder characterized by alternating episodes of depression and mania, often accompanied by varying degrees of cognitive impairment. Cognitive impairments often serve as indicators of a bleak prognosis or the likelihood of progressing to dementia. Additionally, some studies suggest that individuals diagnosed with BD may undergo a decline in hippocampal volume. However, the potential for reversibility of these changes, particularly in adolescents, remains unclear. We present an intriguing case involving an 18-year-old male student who experiences concurrent occurrences of both BD and mild cognitive impairment (MCI), accompanied by a subtle reduction in hippocampal volume. Initially, the individual exhibited impaired general cognitive function, as indicated by an IQ score of 80 on the Standard Raven’s Progressive Matrices test, and demonstrated slightly reduced bilateral hippocampal volume compared to the normative reference, as determined through quantitative structural magnetic resonance imaging (qsMRI). The deposition profiles of amyloid beta (Aβ) peptide in the brain were not identified with 18F-AV45 PET/MRI. Following six months of combined psychopharmacological treatment and cognitive behavioral therapy, the individual’s psychopathological symptoms improved significantly, leading to a restoration of his IQ score to 116 and normalization of hippocampal volume. This case suggests that the hippocampal volume reduction and cognitive impairment seen in some adolescents with BD may demonstrate greater plasticity compared to neurodegenerative conditions such as Alzheimer’s disease (AD). These findings highlight the potential importance of early intervention in young BD patients with cognitive impairments.